Mixed urushiol and laccol compositions in natural lacquers: Convenient evaluation method and its effect on the physicochemical properties of lacquer coatings - Lee, Hanna; Han, Hyemi; Kim, Dongyoung; Lee, Bora; Cho, Jeong Ho; Lee, Yeonhee; Lee, Sang-Soo; Lim, Jung Ah (ELSEVIER SCIENCE SA, 2021)
An evaluation of the catechol lipid compositions of natural lacquer materials and their correlation with the physicochemical properties of lacquer films have become important issues for the advancement of natural lacquer technologies. Here, a convenient method for evaluating the relative composition of urushiol and laccol catechol lipids in natural lacquers using Fourier transform infrared (FT-IR) analysis is proposed. Urushiol and laccol exhibited different characteristic peaks in the FT-IR spectrum owing to the different stereoisomer structures of the conjugated dienes, and the peak positions linearly shifted according to the relative content of the urushiol and laccol components in the natural lacquers. This evaluation method was applicable for estimating the mixing compositions of laccol and urushiol in commercially available natural lacquer products. A quantitative analysis of the physicochemical properties of various lacquer films with urushiol, laccol, and their mixtures confirmed that the hardening speed, mechanical hardness, adhesion, and corrosion resistance deteriorated, whereas the transparency and haze properties improved as the laccol content increased. This study suggests that the estimation and optimization of laccol and urushiol compositions in natural lacquers are an important strategy for improving the physicochemical properties of natural lacquer films and extending their applications in various functional coatings.